2010
DOI: 10.1002/pits.20545
|View full text |Cite
|
Sign up to set email alerts
|

Repeated reading and vocabulary‐previewing interventions to improve fluency and comprehension for struggling high‐school readers

Abstract: Using an adapted alternating treatments design, this study compared the effects of two intervention conditions on the reading fluency, comprehension, and comprehension rate of six high-school students reading below grade level. Students were repeatedly exposed to repeated reading (RR), repeated reading and vocabulary previewing (RR + VP), and no intervention control conditions. Dependent variables were assessed at the end of experimental sessions by using practiced passages. Both interventions had positive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 22 publications
2
34
2
Order By: Relevance
“…Previous studies showed neutral results in testing the variability between reading silently versus aloud (Hawkins et al, 2011;McCallum et al, 2004); however, this study's findings also suggest that silent reading is optimal (Sanden, 2014). Data collected from students from both high-and low-income schools were used, and the results regarding the effects of choice and silent reading on reading comprehension were the same.…”
Section: Conclusion and Implications For Future Researchcontrasting
confidence: 53%
See 1 more Smart Citation
“…Previous studies showed neutral results in testing the variability between reading silently versus aloud (Hawkins et al, 2011;McCallum et al, 2004); however, this study's findings also suggest that silent reading is optimal (Sanden, 2014). Data collected from students from both high-and low-income schools were used, and the results regarding the effects of choice and silent reading on reading comprehension were the same.…”
Section: Conclusion and Implications For Future Researchcontrasting
confidence: 53%
“…The outcomes of studies of both SSR and reading aloud are conflicting or neutral (Hawkins, Hale, Sheeley, & Ling, 2011;McCallum, Sharp, Bell, & George, 2004). Because it is not clear which type of reading has a more positive effect on children's reading comprehension, both variables need further study.…”
Section: Reading Silently Versus Aloudmentioning
confidence: 99%
“…In their own study they found that fluency-based story retell task was "not a strong indicator of reading comprehension skills among fourth grade students" (Bellinger & DiPerna, 2011, p. 425 The research in the literary review suggested that high school students need fluency instruction in the curriculum because evidence showed that a significant number were deficient in this area (Begney et al, 2009;Marchand-Martella et al, 2010;Murray et al, 2012;Paige et al, 2012; Wexler et al, 2010) and they were not receiving instruction needed to improve (Paige et al, 2012; Wexler et al, 2010). Furthermore, the review enumerated the many dangers for secondary students who cannot read fluently (Hawkins et al, 2011;Hudson et al, (2009);McComas et al 2009;Rasinski, 2012; Wexler et al, 2010). These dangers were deemed crucial because today's high school students are THE EFFICACY OF REPEATED READING 38 expected to read at increasingly complex levels called for by College and Career Ready Standards.…”
Section: The Efficacy Of Repeated Reading 36mentioning
confidence: 99%
“…Secondary students who have reading difficulty may take longer than their classmates to accurately decode text (Hawkins, Hale, Sheeley, & Ling, 2011). Rasinski (2012 suggested those slow readers' frustration and lack of interest in reading increases in middle and high school reading when assignments of 30 to 60 minutes become assignments that call for 90 to 180 minutes because of students' lack of reading automaticity.…”
Section: Chapter 2: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation